Sustainable Accounting : Islamic Perspective and The Research Path - Mimma Maripatul Uula; Ihsanul Ikhwan (Accounting and Sustainability, 2022)
This study aims to see the development of research on the topic of "Islamic Sustainable Accounting" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Islamic Sustainable Accounting" which comes from the Dimension database with a total of 42 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Islamic Sustainable Accounting" research development in the world. The results of the study found that in bibliometric author mapping the authors who published the most research with the theme "Islamic Sustainable Accounting" were Ratnasari, Ririn Tri and Wijayanti, Provita. Furthermore, based on bibliometric keyword mapping, there are 3 clusters that can become research paths with topics related to Covid-19 and Islamic Sustainable Accounting, Islamic Microfinance and Islamic Sustainable Accounting, and Entrepreneurship and Islamic Sust ainable Accounting. Furthermore, the most used words are management, development, accounting, and sustainable development.